2021
DOI: 10.3390/polym13223961
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Structural Adhesive Joints in Hybrid Joining Processes

Abstract: Hybrid joining (HJ) is the combination of two or more joining techniques to produce joints with enhanced properties in comparison to those obtained from their parent techniques. Their adoption is widespread (metal to metal joint, composite to composite and composite to metal) and is present in a vast range of applications including all industrial sectors, from automotive to aerospace, including naval, construction, mechanical and utilities. The objective of this literature review is to summarize the existing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 97 publications
0
42
0
1
Order By: Relevance
“…Epoxy resins are extensively used in a wide range of applications [1], including adhesives [2,3], coatings [4,5], and high-performance composites [6,7], among others. However, as one of the main drawbacks is their inherent brittleness, much research has gone into finding ways to increase their toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are extensively used in a wide range of applications [1], including adhesives [2,3], coatings [4,5], and high-performance composites [6,7], among others. However, as one of the main drawbacks is their inherent brittleness, much research has gone into finding ways to increase their toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent mechanical properties, bond properties, insulation properties, thermal stability, alkali resistance, stable chemical properties, and low cost, epoxy adhesive is now widely used in bonding metal or non-metal with thermosetting materials [ 1 , 2 , 3 , 4 , 5 , 6 ], such as the bonding layer between ultrahigh performance concrete (UHPC) and a thin asphalt layer, or the bond of carbon fiber reinforced polymer (CFRP) with fatigue damaged steel structures. However, such examples require epoxy adhesives to have excellent mechanical properties, surface roughness, and toughness, yet unmodified epoxy adhesive composites are too brittle and vulnerable to cracking [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the FSJ method was used to join nonmetallic materials, allowing this method to cover a broader range of materials. In this regard, researchers have shown that, compared with other joining processes, FSJ can improve mechanical properties [15,16]. The variety of polymers that can be subjected to FSJ is not comprehensive.…”
Section: Introductionmentioning
confidence: 99%